Do proteolytic cascades exist in plants? - Paulus, J; van der Hoorn, R (Oxford University Press, 2019)
Proteolytic cascades are hierarchic sets of proteases that activate each other by proteolytic cleavage. Textbook examples are Ser proteases regulating blood coagulation and caspases regulating apoptosis. Many additional proteolytic cascades have been described in animal biology. In plants, however, knowledge on proteolytic cascades is fragmentary. Some plant proteases require non-self processing to become active and vacuolar processing enzymes, subtilase- and papain-like proteases have been implicated in proteolytic cascades. We discuss these examples against four criteria that are set for proteolytic cascades in animal science and conclude that proteolytic cascades are likely to occur in plants but remain to be characterised.